2nd annual rare plant symposium: evening presentation - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2005)
In addition to the daylong Rare Plant Symposium, an informal evening session was held for members of the public interested in rare plants. The event was organized by the Colorado Rare Plant Technical Committee (CoRPTC) and hosted in conjunction with the Colorado Native Plant Society's annual meeting.
Symposium held on September 16, 2005 at the Pagosa Lodge in Pagosa Springs. Held in conjunction with the Colorado Native Plant Society's Annual Meeting.
Presented by the Colorado Rare Plant Technical Committee.
Keywords: Rare plants -- Colorado -- Identification; Endemic plants -- Colorado -- Identification; Endangered plants -- Colorado -- Identification